2022
DOI: 10.3390/plants11212968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Acid Root Exudates of Malus hupehensis Rehd. Derived from Soil and Root Leaching Liquor from Orchards with Apple Replant Disease

Abstract: Organic acids secreted by plants, such as p-hydroxybenzoic acid, ferulic acid, cinnamic acid, and benzoic acid, can inhibit seed germination and root growth. The effects of root and soil leaching liquor from orchards on the growth of M. hupehensis Rehd. seedlings under sand culture are studied; the seedlings are sampled at 15, 30, 45, and 60 d. Changes in the amount of root exudates are determined using HPLC. Low concentrations of root leaching liquor (A1) and soil leaching liquor (B1) significantly promoted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This is due to the soil itself has a specific buffering capacity. Application of quantitative amount of biochar does not change the pH of the soil evidently, which corresponds to the previous conclusion [45,46]. The EC values of the B@PM group (10TJ, 20TJ, and 30TJ) were greater than those of CS, T, and J.…”
Section: Effect Of B@pm On Soil Physico-chemical Properties and Enzym...supporting
confidence: 88%
“…This is due to the soil itself has a specific buffering capacity. Application of quantitative amount of biochar does not change the pH of the soil evidently, which corresponds to the previous conclusion [45,46]. The EC values of the B@PM group (10TJ, 20TJ, and 30TJ) were greater than those of CS, T, and J.…”
Section: Effect Of B@pm On Soil Physico-chemical Properties and Enzym...supporting
confidence: 88%
“…Though secretion of these compounds is considered a defense response, it is hypothesized that high levels of phenolic compounds can have autotoxic effects, potentially exacerbating ARD. Additionally, it was shown that genes associated with the production of caffeic acid were upregulated in ARD- infected apple roots, relative to those grown in γ-irradiated ARD soil 66,67 , and that root and soil extracts from replant-diseased trees inhibited apple seedling growth and resulted in increased seedling root production of caffeic acid 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species have the potential to cause significant cell damage. Indeed, phenolic compounds appeared to reduce seedling growth of crop 38 . Meanwhile, phenol structures caught hold of the behaviour of respiratory enzymes.…”
Section: Discussionmentioning
confidence: 99%